2022
DOI: 10.1186/s41110-022-00161-z
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and vegetable consumption during the COVID-19 lockdown in Sri Lanka: an online survey

Abstract: Purpose The COVID-19 pandemic has drastically altered the dietary patterns of individuals. This study aimed to investigate the changes in the purchase and consumption of fruit and vegetables in Sri Lanka during the COVID-19 pandemic. Methods An online cross-sectional survey assessed the self-reported changes in fruit and vegetable consumption and purchase using Google forms. Logistic regression analyses were performed to assess the association betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 46 publications
3
8
1
Order By: Relevance
“…Fruit consumption has decreased since the COVID-19 pandemic. This finding is consistent with previous studies showing a reduction in fruit consumption [ 23 , 24 ]. A previous study reported that this decreasing trend is higher among food-insecure individuals than food-secure individuals [ 25 ].…”
Section: Discussionsupporting
confidence: 94%
“…Fruit consumption has decreased since the COVID-19 pandemic. This finding is consistent with previous studies showing a reduction in fruit consumption [ 23 , 24 ]. A previous study reported that this decreasing trend is higher among food-insecure individuals than food-secure individuals [ 25 ].…”
Section: Discussionsupporting
confidence: 94%
“…However, the per capita expenditure on fresh fruit and vegetables in the fourth quarter of 2020 grew less than the per capita expenditure on other food products. Our results are also consistent with studies conducted by Sooriyaarachchi et al. (2022) whose findings show that the consumption of locally produced fruit and vegetables during the pandemic period has increased considerably.…”
Section: Discussionsupporting
confidence: 93%
“…The paper contributes to the recent literature about changes in consumption habits due to COVID-19 (e.g. Ammann et al ., 2022; Dumitras et al ., 2021; Güney and Sangün, 2021; Sooriyaarachchi et al ., 2022). In particular, the findings show the long-term effects of the pandemic on consumers' behavior and consumption of fruit and vegetables.…”
Section: Introductionmentioning
confidence: 99%
“…This study was conducted in Sri Lanka as a part of a nationallevel cross-sectional online survey that aimed to investigate the immediate impact of the COVID-19 pandemic on lifestylerelated behaviors. A detailed description of the study population, methods, and the impact on other lifestyle patterns have been published elsewhere [13][14][15]. Data were collected through a self-administered questionnaire accessible through the Google Forms web survey platform.…”
Section: Study Population and Samplementioning
confidence: 99%
“…The research was performed in accordance with the principles of the Declaration of Helsinki. The authors declared that the protocol of this article was part of a previously published [12][13][14] large initiative in Sri Lanka (2021-2022). Moreover, web-based informed consent was obtained from each participant after explaining the study objectives and the guarantee of secrecy.…”
Section: Fundingmentioning
confidence: 99%